Identification of allelic relationship and translocation region among chromosomal translocation lines that leads to less-seed watermelon - Jiao, Di; Zhao, Hong; Sun, Honghe; Zhang, Jie; Zhang, Haiying; Gong, Guoyi; Anees, Muhammad; Zhu, Hongju; Liu, Wenge; Xu, Yong (Horticulture research, 2024)
Less-seed and seedless traits are desirable characteristics in watermelon (Citrullus lanatus). Hybridization between watermelon chromosomal translocated lines and wild lines significantly reduced seed counts in the hybrid fruits, approaching even seedless. However, the allelic relationships and the chromosomal translocation breakpoints from different sources are unclear, which limits their utility in breeding practices. This study focused on three groups of chromosomal translocation materials from different sources and conducted inheritance and allelic relationship analysis of translocation points. The results from third-generation genome sequencing and fluorescence in situ hybridization (FISH) revealed that the specific translocations in the naturally mutated material MT-a involved reciprocal translocations between Chr6 and Chr10. The Co60γ radiation-induced mutant material MT-b involved reciprocal translocations between Chr1 and Chr5, Chr4 and Chr8. The Co60γ radiation-induced mutant material MT-c involved complex translocations among Chr1, Chr5, and Chr11. Cytological observation showed that heterozygous translocation hybrids showed chromosomal synapsis abnormalities during meiotic diakinesis. Further, dominant and codominant molecular markers were developed on both sides of the translocation breakpoints, which could facilitate rapid and efficient identification of chromosome translocation lines. This study provides technical guidance for utilizing chromosomal translocation materials in the development of less-seed watermelon varieties.